Social Capital as Obstacle to Development: Brokering Land, Norms, and Trust in Rural India. (October 2015) - Levien, Michael
Summary: Based on a study of how rural land brokers mediate the arrival of a Special Economic Zone in rural Rajasthan, this paper argues that theories of collective social capital cannot explain how networks, norms, and trust interact in a process of economic change. It then reconstructs Bourdieu's distinct theory of individual social capital by showing how better-connected farmers are able to broker land and capture profits at the expense of fellow villagers, undermining trust, norms, and collective action. It argues that social capital is most plausibly seen as an aspect of social inequality that hinders inclusive development.